The Genealogical Sublime - Creet, Julia, 1958- (Book collections on Project MUSE., 2020)
"Since the early 2000s, genealogy has become a lucrative business, an accelerating online industry, a massive data mining project, and fodder for reality television. But the fact remains that our contemporary fascination with family history cannot be understood independently of the powerful technological tools that aid and abet in the search for traces of blood, belonging, and difference. In The Genealogical Sublime, Julia Creet traces the histories of the largest, longest-running, most lucrative, and most rapidly growing genealogical databases to delineate a broader history of the industry. As each unique case study reveals, new database and DNA technologies enable an obsessive completeness-the desire to gather all of the world's genealogical records in the interests of life beyond death. Archival research and firsthand interviews with Church of Jesus Christ of Latter-Day Saints officials, key industry players (including Ancestry.com founders and FamilySearch executives), and professional and amateur family historians round out this timely and essential study."--